The Response of DC-Link Capacitance in a PWM Converter Inverter - Choeisai, Krit; Prasertcharoensuk, Vichai; Jantakun, Adirek (Engineering and Applied Science Research, 2015)
This paper presents the response of DC-Link capacitance in a PWM Converter Inverter by studying and simulation. The simulation effects that DC-Link capacitance changed. The results showed that the voltage ripple of the DC-Link and total harmonics distortion of input current varied to the capacitance and the switching frequency which use to generate the PWM signal.